1999
DOI: 10.1088/0953-8984/11/48/321
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the vibrational spectra of amorphous silicon on the defect concentration and ring distribution

Abstract: The Raman spectra of nine 216-atom models of amorphous silicon (a-Si) are calculated using the bond polarizability approximation of Raman scattering. These a-Si models, generated by the activation relaxation technique, have different concentrations of coordination defects, ring statistics and local strain distributions, which cause changes in the vibrational density of states and the Raman scattering. Analysis of the vibrational modes indicates that an increase in the number of coordination defects leads to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 42 publications
3
30
0
Order By: Relevance
“…It is seen from Table 1 that as T s increases from 100 to 250°C, the ratios of I LA /I TO and I LO /I TO decrease from 0.257 and 0.590 down to 0.230 and 0.574, respectively. It was reported that responsible for the LA mode are primarily the closed rings configuration and the three-coordinated defects of atoms [13,17]. In our present study, the decrease in LA strength can therefore be attributed to the reduction of the silicon coordination defects and the closed rings in the amorphous network due to a higher T s .…”
Section: Amorphous Networksupporting
confidence: 53%
See 2 more Smart Citations
“…It is seen from Table 1 that as T s increases from 100 to 250°C, the ratios of I LA /I TO and I LO /I TO decrease from 0.257 and 0.590 down to 0.230 and 0.574, respectively. It was reported that responsible for the LA mode are primarily the closed rings configuration and the three-coordinated defects of atoms [13,17]. In our present study, the decrease in LA strength can therefore be attributed to the reduction of the silicon coordination defects and the closed rings in the amorphous network due to a higher T s .…”
Section: Amorphous Networksupporting
confidence: 53%
“…The TA mode intensity at about 150 cm -1 is considered to be proportional to the density of dihedral angle fluctuations, reflecting the medium-range order (MRO) of amorphous network [12]. The existence of coordination defects is necessary for the presence of the LA band at 300 cm -1 and the LO band at 410 cm -1 [13]. The peaks at about x 2LA = 610 cm -1 and x 2TO = 960 cm -1 are overtones of the main a-Si x LA and the main a-Si x TO , respectively.…”
Section: Amorphous Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…PC-K1EDIP1, which has no D 1 or D 2 defects, exhibits a much higher p c () at the 90 cm Ϫ1 band edge. The main difference in the participation ratio between the PC models and the WWW CRN model 37 as well as a-Si models generated by the activation-relaxation technique ͑ART͒, 47 investigated previously, 36,48 is that the CRNs do not show low-frequency localization. However, CRN models of a-Si produced with the Biswas, Grest, and Soukoulis method 42 also exhibit low-frequency localization on undercoordinated atoms, which implies that such features are not specific to the PC structure, or the SW potential or EDIP.…”
Section: B Vibrational Modesmentioning
confidence: 92%
“…They are located predominantly on D 3 atoms. Such modes are not observed in CRN models generated by the WWW 36 or ART 48 methods. The general character of the total phase quotient q ⌺ (), shown in Fig.…”
mentioning
confidence: 89%